Preservation of Local Wisdom Values in Culture of Sundanese, Balinese, Lombok, and Dayak Kalimantan Communities: A Comparative Study Traditions, Beliefs, and Artistic Expressions - Marzuti Isra; Tadzkia dina arika; Viya Nur Sucianti Purba; Akhmad Azhari Nasution; Ahmadi Hasibuan; Pertin Lumban Gaol (Jurnal Multidisiplin Sahombu, 2025)
The preservation of local wisdom values is a crucial effort in maintaining cultural identity and social harmony within communities. This study examines the origins and forms of local wisdom preservation in the cultures of the Sundanese, Balinese, Lombok, and Dayak Kalimantan societies through a comparative approach. The local wisdom explored in this research emerges from historical experiences, interactions with the natural environment, and distinctive belief systems in each region. Traditions such as seren taun in Sundanese culture, Hindu religious ceremonies in Bali, Sasak practices in Lombok, and Dayak rituals reflect artistic expression and spiritual values that are still maintained today. The findings indicate that preservation efforts are supported by community roles, traditional leaders, and adaptation to social change. It is recommended that an integrative approach be adopted to sustain local wisdom values effectively.